Peningkatan Hasil Belajar Siswa Pembelajaran Seni Tari Melalui Model STAD Kelas VIII SMPN 34 Kerinci - Indah Dean Azzahra; Yuliasma Yuliasma (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2024)
Education is something that is very important and needed by every individual which can have a positive influence on a person's growth and development. Education is usually provided through the learning process at school. Learning is a process of interaction between teachers and students in forming the students' own character which involves cognitive, affective and psychomotor aspects. The success of the learning process can be seen from the learning outcomes obtained by students. The problem of low student learning outcomes became the attention of researchers in carrying out this research. The STAD learning model is an alternative solution in this research in order to improve student learning outcomes. So, the aim of this research is to improve student learning outcomes in dance subjects through the STAD model in class VIII A of SMP Negeri 34 Kerinci. The research method used in this research is classroom action research (PTK). The data collection technique used is a written test to determine student learning outcomes. The results of this research indicate that the STAD learning model can improve student learning outcomes. This is shown by the average student learning outcomes which were initially only 45.7, increasing to 92.8 after implementing the STAD model.